An Expository Discourse on Discretionary Punishment and its Application in Theft Cases Under the Islamic Law - Owoade, A. A. (NIU Journal of Humanities; Vol 2 No 1 (2017): KIU Journal of Humanities, Vol. 2 No. 1, June 2017, 2017)
Islam has conferred and granted the right of security of ownership of property and emphasized on respect therein to take good care of every item owned by someone. It is further recognized by the Shariâ€™ah that it is the duty of every rich Muslim to pay out a certain amount from his/her wealth as charity to the poor and needy Muslims. Likewise Islam gives the latitude of acquiring the use of oneâ€™s property through mutual consultation and agreement by (borrowing or loan) and the rich Muslims should not deny their brother Muslims from benefitting from his wealth or properties. Thus, these are the rights that Islam gives to Muslim brothers among themselves, but these right could not be misused by taking things of another without his/her consent, if so, it amounts to theft. In view of the above, it is my humble opinion that if all the Muslim community and the government have fulfilled their obligation towards their brother Muslims, and went ahead to take someoneâ€™s property, it amounts to theft under Shariâ€™ah Law. Therefore, Muslims are enjoined to keep aloof from such actions and alike, the Holy Qurâ€™an in Surat al-Baqarah verse 188 provides as follows: â€œAnd do not eat up your property among yourselves for vanities, nor use it as bait for the judges, with intent that ye may eat up wrongfully and knowingly a little of (other) peopleâ€™s propertyâ€.  As to the above quotation, Muslims are enjoyed to move away from committing the offence of theft, for it is a great offence under Islamic Law. One should not by all means apply or attempt eating up someoneâ€™s wealth wrongfully. Thus, robberies, embezzlement, using someoneâ€™s property to corrupt others directly or indirectly amount to atrocity and abominable tasks prohibited by Allah. These also apply to public properties under the control and management of the rulers to take good care in order to avoid converting them into their personal use. Therefore, one can realize that the prohibition of this offence through the sever punishment prescribed for it, (i.e. amputation of the theftâ€™s hand) would not allow a man of piety to engage in such an evil deed.